Multiplex Conditional Mutagenesis Using Transgenic Expression of Cas9 and sgRNAs. Issue 2 (8th April 2015) - Yin, Linlin; Maddison, Lisette A; Li, Mingyu; Kara, Nergis; LaFave, Matthew C; Varshney, Gaurav K; Burgess, Shawn M; Patton, James G; Chen, Wenbiao
Abstract: Determining the mechanism of gene function is greatly enhanced using conditional mutagenesis. However, generating engineered conditional alleles is inefficient and has only been widely used in mice. Importantly, multiplex conditional mutagenesis requires extensive breeding. Here we demonstrate a system for one-generation multiplex conditional mutagenesis in zebrafish ( Danio rerio ) using transgenic expression of both cas9 and multiple single guide RNAs (sgRNAs). We describe five distinct zebrafish U6 promoters for sgRNA expression and demonstrate efficient multiplex biallelic inactivation of tyrosinase and insulin receptor a and b, resulting in defects in pigmentation and glucose homeostasis. Furthermore, we demonstrate temporal and tissue-specific mutagenesis using transgenic expression of Cas9. Heat-shock-inducible expression of cas9 allows temporal control of tyr mutagenesis. Liver-specific expression of cas9 disrupts insulin receptor a and b, causing fasting hypoglycemia and postprandial hyperglycemia. We also show that delivery of sgRNAs targeting ascl1a into the eye leads to impaired damage-induced photoreceptor regeneration. Our findings suggest that CRISPR/Cas9-based conditional mutagenesis in zebrafish is not only feasible but rapid and straightforward.